Program KKN DR: Pembuatan Hand sanitizer sebagai Upaya Memutus Rantai Penyebaran Virus COVID-19: - Feti Nur Laily; Imam Rofiki (Institute for Research and Community Services, 2023)
The program of KKM DR is a community service program during covid-19 pandemic. This activity was carried out in groups for 30 days in their respective domiciles. Due to the covid-19 pandemic, residents must maintain hand hygiene by washing their hands. Excessive use of water will cause waste. Therefore, another alternative is needed to replace clean water to keep hands clean, namely by using a hand sanitizer. The soaring price of hand sanitizers is the reason for conducting hand sanitizer production. The program implementation include health socialization and hand sanitizer production for Plumbon Gambang villagers. The purpose of this KKM DR activity is to provide knowledge and insight to the public about harms of the covid-19, and the importance of maintaining hand hygiene. There were 25 people involved in this program. The method used was Asset Based Community Development (ABCD). This activity produces hand sanitizer products that the community can use to maintain cleanliness. With hand sanitizer production activities, the community is expected to know how to make hand sanitizers properly. The results of this program showed that 92% of Plumbon Gambang villagers were very enthusiastic about participating in health socialization and hand sanitizer production programs.